COMPARATIVE EFFICIENCY OF VARIOUS SCHEMES OF TREATMENT OF MENOPAUSAL DISORDERS - N. V. Spiridonova; N. V. Basina; O. V. Krylova (Акушерство, гинекология и репродукция)
Menopause is usually accompanied by vividly expressed clinical symptoms and the condition of hypomagnesemia. During the course of oral magnesium preparations therapy, the health normalization of the patients takes place, as well as the magnesium concentration in blood also comes to the norm. It seems to be reasonable to appoint the magnesium preparations to women with normal quality of life, if there is a necessity of isolated correction of menopausal disorders with light or medium severity, and also to the patients with hard severity of the disease with a predominance of psychoemotional disorders, in combination with contraindications to the standard hormone replacement therapy or when the patient refuses from receiving the hormone replacement therapy.